2005
DOI: 10.2307/30035948
|View full text |Cite
|
Sign up to set email alerts
|

Are Immigrant Remittance Flows a Source of Capital for Development?

Abstract: The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMP or IMF policy. Working Papers dei\Cribe research in progress by the author(s) and are published to elicit comments and to further debate.The role of remittances in development and economic growth is not well understood, 1bis is partly because the literatures on the causes and effects of remittances remain separate, We develop a framework that links the motivation for remittances with their eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(65 citation statements)
references
References 50 publications
0
63
1
1
Order By: Relevance
“…A few other studies (including Durand et al, 1996;Massey & Parrado, 1998;Faini, 2003;Ratha, 2003;Pradhan et al, 2008;Siddique et al, 2012;Das & Chowdhury, 2011;Azam & Khan, 2011) have also found that remittances have positive impact on economic growth as remittance receipts affects domestic savings and overall growth of output positively. However, the studies like Chami et al (2005) Karagoz ( 2009) Tehseen and Raza (2012) found contrasting results as their findings suggest that remittances have negative or zero impact on economic growth.…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…A few other studies (including Durand et al, 1996;Massey & Parrado, 1998;Faini, 2003;Ratha, 2003;Pradhan et al, 2008;Siddique et al, 2012;Das & Chowdhury, 2011;Azam & Khan, 2011) have also found that remittances have positive impact on economic growth as remittance receipts affects domestic savings and overall growth of output positively. However, the studies like Chami et al (2005) Karagoz ( 2009) Tehseen and Raza (2012) found contrasting results as their findings suggest that remittances have negative or zero impact on economic growth.…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…The relationship between remittance inflows and economic growth has been widely investigated by several researchers (Barajas et al, 2009;Chami et al, 2003Chami et al, , 2005Goschin, 2014;Konan & N'Zué, 2019;Kumar & Stauvermann, 2014;Lim & Simmons, 2015;Matuzeviciute & Butkus, 2016;Meyer & Shera, 2017). However, there are only few papers dedicated to the link between remittance outflows and macroeconomic factors (Al-Abri et al, 2018;Al Kaabi, 2016;Alkhathlan Khalid, 2013;Baas & Melzer, 2012;Bobeva, 2017;Edrees, 2016;Hathroubi & Aloui, 2016;Naufal & Genc, 2017;Razali et al, 2016;Termos et al, 2013;Vargas-Silva & Huang, 2006).…”
Section: Brief Review Of Selected Literaturementioning
confidence: 99%
“…Some of the studies focused on the effect of migration at the household level from the pessimistic point of view where the effects of remittances are viewed as rarely productive. For instance, De Haas (2005), Chami et al (2005), and Lipton (1980) argued that a major portion of remittances of the migrant households is used for daily consumer spending. In contrast, the optimists show multiple positive contributions of remittances to the households including savings, investment, acquire assets, accumulation of human capital, and use of modern technology (De & Ratha, 2012;Gardner & Ahmed, 2009;Mahapatro, 2016;Mendola, 2008;Sharma & Zaman, 2009).…”
Section: Assessing the Impact Of Migration On Household Welfarementioning
confidence: 99%